PHYTOCHEMICAL SCREENING AND ANTIFUNGAL ACTIVITIES OF Mitracarpus scaber CRUDE EXTRACTS ON SOME PATHOGENIC FUNGI. - Muhammmad, I. L.; Muhammad, R. G.; Kassim, Z. J.; Ndatsu, Y.; Mohammed, U. B.; Suleiman, A. L. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2017)
Preliminary phytochemicals screening of acetone, aqueous and methanol extracts of Mitracarpus scaber was carried out using Harbone and Hassan’s method. The phytochemical screening of acetone extract revealed the presence of anthroquinone, flavonoids, saponin and tannin, while methanol extract possessed anthroquinone, saponin, steroid, flavonoids and tannins. However, aqueous extract revealed the presence of tannins and flavonoids, while alkaloid, terpenes, resin, reducing sugar were absent in all extracts. The antifungal activities of acetone, aqueous and methanol extracts of Mitracarpus scaber were analysed using discs diffusion method. After 72 hours of incubation, both extracts at 10mg/disc inhibited the growth of Aspergillus fumigatus, Aspergillus flavus, Aspergillus niger, Mucor mucedo, Microsporium canis, Fusarium solani, Candida albican, Epidermophyton floccosum and Trichopyton verrucosum. The methanol extract of Mitracarpu sscaber was more active than acetone and aqueous extracts. The activities of the extracts may be responsible for their utilization in the traditional treatment of various ailments associated with the test organisms.